Allocation of resources in medicine – a moral imperative for doctors as well. (October 2020) - Mallia, Pierre
Abstract: Allocation of resources remains one of the most onerous tasks in medicine and in departments of health. Increases in novel technologies and new drugs portray a bright future but with a tag of higher costs. This has created a moral imperative for doctors when choosing tests and treatment to make ever more responsible choices. Doctors should be leaders and involve themselves from macro- and meso-levels of planning allocation to the micro-level where contact with patients occurs. Over-prescription of tests can result from an outdated mode of fidelity to individuals without consideration that everyone in some way or another pays for those tests or treatment being ordered, and includes has come to be known as defensive practice to avoid lawsuits. With appropriate research and support from guidelines, medico-legal issues can be adequately allayed while maintaining a high standard of care taking micro-resource allocation more professionally into consideration.